Magnesium‐Mediated Electrochemical Synthesis of Ammonia - Ishita Goyal; Vamsi V. Gande; Rajan R. Bhawnani; Rebecca Hamlyn; Ahmed A. Farghaly; Meenesh R. Singh (Advanced Science, 2025)
Abstract Metal‐mediated electrochemical synthesis of ammonia (NH3) is a promising method to activate N2 at room temperature. While a Li‐mediated approach has been optimized to produce NH3 at high current density and selectivity, Li's scarcity and its highly negative plating potential limit scalability and energy efficiency. Alternative mediators have been proposed, but only Ca has shown some promise, achieving ≈50% Faradaic efficiency (FE), though requiring voltages beyond −3 V. Here, we report a Mg‐mediated nitrogen reduction reaction (Mg‐NRR), where N2 is activated on Mg to form Mg3N2, followed by protolysis to release NH3 and regenerate Mg. A notable NH3 FE of 25.28 ± 3.80% is achieved at a current density of −45 mA cm−2, corresponding to an NH3 partial current density of −11.30 ± 1.77 mA cm−2 under 6 bar N2. Isotope‐labeled experiments confirm that NH3 originates from N2, with similar FE (25.15 ± 1.01%). Importantly, NH3 production is demonstrated at a total cell potential as low as −3 V. This Li‐free Mg‐NRR system offers key advantages, including lower energy input and use of earth‐abundant materials, making it a scalable route for sustainable NH3 synthesis.